Improved DNA methylation analysis via enrichment of demethylated cells expressing an X-inactivated transgene - Vallender, Tammy W (BioTechniques, 2006)
The demethylating drug 5-aza-2'-deoxycytidine (5-aza-2dC) is frequently used to investigate the effect of global DNA demethylation on gene expression in cultured mammalian cells. Here, we describe a method that uses the reactivation of an X-inactivated green fluorescent protein (GFP) transgene as a marker to enrich for cells that have undergone drug-induced demethylation. By combining it with microarray gene expression profiling, we demonstrate the method's utility in identifying genes activated by global DNA demethylation